2007
DOI: 10.1007/s10350-007-9037-y
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Nonpolyposis Colorectal Cancer (Lynch Syndrome) in Argentina: Report from a Referral Hospital Register

Abstract: PURPOSE: The first Argentine experience with epidemiologic, molecular, and genetic counseling data is reported. METHODS: We analyzed 43 families fulfilling Amsterdam criteria identified from a prospective database with data from 779 relatives. RESULTS: Eleven families (25.6 percent) presented as Lynch I, 29 (67.4 percent) as Lynch II, and 3 (7 percent) as Muir-Torre syndrome. Among the 306 affected members, 197 cases of colorectal cancer were identified (mean age at diagnosis, 52.1 (range, 21-90) years). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
11
0
3
Order By: Relevance
“…A study of South American LS families from Brazil (101 families), Argentina (16 families) and Uruguay (6 families), demonstrated that 56.3% of the MMR mutations were found on the MLH1 gene [28]. In contrast, a different report of 43 unrelated Argentinian families that fulfill Amsterdam criteria, for which 5 mutations were encountered, most of these were found at the MSH2 gene, similar to our Caribbean Hispanics [35]. Differences in the spectrum of MMR mutations between Hispanic populations could be due to differences in the, sample size, selection bias, as well as, genetic ancestry of the individual populations.…”
Section: Discussionsupporting
confidence: 70%
“…A study of South American LS families from Brazil (101 families), Argentina (16 families) and Uruguay (6 families), demonstrated that 56.3% of the MMR mutations were found on the MLH1 gene [28]. In contrast, a different report of 43 unrelated Argentinian families that fulfill Amsterdam criteria, for which 5 mutations were encountered, most of these were found at the MSH2 gene, similar to our Caribbean Hispanics [35]. Differences in the spectrum of MMR mutations between Hispanic populations could be due to differences in the, sample size, selection bias, as well as, genetic ancestry of the individual populations.…”
Section: Discussionsupporting
confidence: 70%
“…The mutation spectrum is predominated by MLH1 (60%) and MSH2 (40%) mutations [3,19-22], but the seemingly larger contribution than the 42% and 33% reported in the InSIGHT database could reflect failure to test for MSH6 and PMS2 mutations in most South American studies [1]. Referral bias in populations that have more recently been screened for mutations represents a potential limitation, but the strong contribution from MLH1 and MSH2 could also reflect population structure [2,4,5,7]. Frameshift mutations and nonsense mutations were the most common types of mutations, which are in agreement with findings from other populations [1,23-26], with hotspots in exons 16 and 18 of MLH1 and in exon 13 of MSH2 (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, Colombia, Peru and Bolivia, Spanish colonist and American Indian ancestry influence the populations [2,3]. Mutation screening in South American families suspected of Lynch syndrome has identified disease-predisposing germline mutations in MLH1 and MSH2 in 16-45% of families that fulfill the Amsterdam criteria and/or the Bethesda guidelines [2-7]. Hereditary colorectal cancer registries have been established in Argentina, Brazil, Uruguay and Chile with the aim to collect and share data on the MMR gene mutation spectrum, identify potential founder mutations, interpret the role of unclassified genetic variants and to study cancer risks in the South American Lynch syndrome population.…”
Section: Introductionmentioning
confidence: 99%
“…In a review published by Dominguez-Valentín et al, the LS mutation spectrum in South American countries was described [62]. Pathogenic mutations in the MMR genes were identified in patients from Brazil [53], Argentina [63], Uruguay [64], and Colombia [65] (Table 3). Furthermore, the InSIGHT database contains additional information on MMR mutations in additional Hispanic subpopulations, Portugal, and Spain [53].…”
Section: Introductionmentioning
confidence: 99%